Breast pathology after cryotherapy. Histological regression of breast cancer after cryotherapy - Gajda, Mieczyslaw R.; Mireskandari, Masoud; Baltzer, Pascal A.; Pfleiderer, Stefan O.; Camara, Oumar; Runnebaum, Ingo B.; Kaiser, Werner A.; Petersen, Iver (Polish Journal of Pathology, 2014)
A breast saving treatment is contemporary the preferred method of treatment with comparable results in comparing with mastectomy. In this study were evaluated the effects of cryotherapy by histological verification of changes in post treatment resection specimens. Fifty-three patients in age of 38-81 year with histologically confirmed breast cancer in needle biopsies were managed by cryotherapy between 1999 and 2007. The patients were operated between day 1 and 35 after cryotherapy. The histologic examination of operation materials showed in all cases at least partial tumor destruction. In general in 54.7% of all handled cases (29 patient) there was no residual tumor. In 6 cases (22.2%) from group 1 and in 23 cases (88.5%) of group 2 no tumor rest was found. Cryotherapy can lead to complete destruction of tumoral tissue. In our study all 29 (54.7%) of tumor-free cases after cryotherapy were those with cT1 stage. The experience of operator and the correct selection of appropriate patients (primarily taking the tumor size into account) play the most important role for achieving the best results.